Development and Evaluation of a Variable-Rate Fertilizer Distribution System for Coffee Plants - Murilo Machado de Barros; João Paulo Barreto Cunha; Fagner Goes da Conceição; Carlos Eduardo Silva Volpato; Gabriel Araújo e Silva Ferraz; Fabio Moreira da Silva (AgriEngineering)
Currently, Brazilian coffee farming seeks the rational use of resources through sustainable practices. As a result, the development of machinery with more efficient input application systems and the adoption of precision agriculture techniques have been yielding excellent results. This study was divided into two stages, with the first involving the adaptation of a solid fertilizer application machine with fixed doses, allowing dose variation using an electronic controller. The second stage consisted of conducting trials and their applications under operational conditions. The results confirmed that the developed system remained stable in terms of variable-rate fertilizer distribution for coffee cultivation. The machine’s lateral fertilizer distribution range met the demands of coffee farming satisfactorily. In field conditions, the developed system exhibited an average error of −2.9%, compared to the programmed doses, validating the accuracy of the machine and its suitability for use in coffee plantations.